PSYCHOLOGICAL STUDY OF THE PROCESS OF SOCIALIZATION IN ADOLESCENTS - Laylo Ilhombayevna Kutlimuratova (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the process of socialization in adolescents and the relationship between this process and the society will be highlighted. , is a continuous process that develops depending on moral concepts.